COMPLIANCE TO THE EDUCATION SERVICE CONTRACTING (ESC) REQUIREMENTS BY PARTICIPATING SCHOOLS TOWARDS SUSTAINABILITY OF THE PROGRAM - Bucu, Aljon S. (International Journal of Psychosocial Rehabilitation, 2020)
Quality graduates is often times equated with quality education services. This analogy simply advocates the necessity to promote an ambiance of learning equipped with effective delivery of educational programs and services geared towards skills development on both theoretical and practical aspects. The research paper aimed to describe the compliance to the education service contracting (ESC) requirements by participating schools towards sustainability of the program. The research employed descriptive-evaluative research design to assess the effectiveness of an existing program of the five private schools in Congressional Area 1 which are recipients of the ESC program of the government. Their compliance to DepEd minimum standards was assessed using the actual tool during accreditation/re-certification period in which administrators, teaching & non-teaching including student-leaders were selected as legitimate respondents. Findings revealed that on the nine (9) areas of quality practices and conditions, schools were found practicing the minimum standards to a great extent. This implies that the program beneficiaries conformed to the criteria or standards set by the Private Education Assistance Committee (PEAC) which is the trustee of the Fund for Assistance to Private Education (FAPE). Moreover, the result reported that there is about 88% to 100% compliance level of these schools to DepEd requirements which further indicates that each provision is extensively and functionally met. This implies that there is a perceived a continuous effort in improving the quality of basic education services among these private schools. Based on the conclusion of the study, it can be recommended that promisingly schools have manifested continuous improvement in so far as compliance to basic requirements is concerned. The increasing number of school population specifically on the number of ESC grantees as well as in the number of teaching staff who benefited from the program through a subsidy signals an appropriate and lawful adherence to existing guidelines and conditions.